CLASSIFICAÇÃO DO USO DA TERRA E COBERTURA VEGETAL DA MICROBACIA DO CÓRREGO DO SÍTIO, BACIA DO RIO TAQUARI, COXIM, MS - ARAÚJO, Josias Arruda; ROCHA, Rodrigo; SILVA, Érica Martins; GÜNTZEL, Adriana Maria; OLIVEIRA, Vincler Fernandes Ribeiro (ANAIS DO ENIC, 2020)
-